Digestible threonine-to-lysine ratio in diets for brown egg-laying hens - Lelis, Guilherme R. (2019)
The objective of this study was to evaluate the levels of digestible threonine to determine the ideal digestible threonine-to-lysine ratio in the diet of brown egg-laying hens aged 42-54 wk. A total of 270 Dekalb Brown hens were used in a completely randomized design (5 treatments x 9 replicates x 6 birds = 270 birds). Five different ratios of digestible threonine-to-lysine were evaluated: 66% (0.435% Thr dig), 70%, 74%, 78%, and 82%. The diets were formulated to satisfy the animals' nutritional requirements and amino acid relationships (2,950 Kcal/Kg ME and 14.81% CP), with the exception of threonine and lysine. The ratio of digestible threonine-to-lysine was obtained by L-Threonine (98%) supplementation in place of starch. Parameters such as feed intake (g/bird/d), egg production (%), egg weight (g), egg mass (g), feed (kg/dz and g/g), relative weight of egg components (% yolk, albumen, and eggshell), and weight gain (g) were evaluated. As a result, feed intake, egg weight, relative weight of egg components, and weight gain were found not to be influenced by the digestible threonine-to-lysine ratio used. Egg production, egg mass, and feed conversion (kg/dz and g/g) displayed a quadratic effect for the different ratios used. Based on the results, the digestible threonine-to-lysine ratio recommended in the diets of laying hens between 42 and 54 wk of age is 72%, which corresponds to 0.478% of digestible threonine or 460 mg/bird/d of digestible threonine.